PERSEPSI PEGAWAI ATAS PERAN AUDITOR INTERNAL DI UNIVERSITAS BENGKULU - Siti Aisyah; Yoan Happy Gusmara (Jurnal Akuntansi, 2016)
Ideally, there is no difference perceptionbetween members of an organization toward internalauditor roles. This study identified the perceptionbetween employees and lecturers of University ofBengkulu; whether the internal auditor as audit snoop,consultant, or Management representative. Data isanalyzed using independent sample t test. The researchresults show that there are difference perceptionsbetween employee and lecturers toward the role ofinternal auditor as audit snoop and as a consultant.However, this study found no difference perceptionsamong them on the role of internal auditor asmanagement’s representative. Major role of internalauditor according to employee and lecturers at theUniversity of Bengkulu is the role of as a consultant.Keywords : Internal Auditor, Role, Audit Snoop,Consultant, Management’s Representative.